2016
DOI: 10.1155/2016/3618402
|View full text |Cite
|
Sign up to set email alerts
|

How Environmental Uncertainty Moderates the Effect of Relative Advantage and Perceived Credibility on the Adoption of Mobile Health Services by Chinese Organizations in the Big Data Era

Abstract: Despite the importance of adoption of mobile health services by an organization on the diffusion of mobile technology in the big data era, it has received minimal attention in literature. This study investigates how relative advantage and perceived credibility affect an organization's adoption of mobile health services, as well as how environmental uncertainty changes the relationship of relative advantage and perceived credibility with adoption. A research model that integrates relative advantage, perceived c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…Finally, the aim of this study was to examine the impact of sociality and media characteristics on citizens' perceived value and continuous use of the mobile government microblog. Other factors such as credibility [49] and public-private partnership [50] might also have impacts on citizens' mobile government microblog usage behaviors. Further studies are thus encouraged to examine the influences of credibility and public-private partnership on citizens' continuance behavior.…”
Section: Limitation and Future Workmentioning
confidence: 99%
“…Finally, the aim of this study was to examine the impact of sociality and media characteristics on citizens' perceived value and continuous use of the mobile government microblog. Other factors such as credibility [49] and public-private partnership [50] might also have impacts on citizens' mobile government microblog usage behaviors. Further studies are thus encouraged to examine the influences of credibility and public-private partnership on citizens' continuance behavior.…”
Section: Limitation and Future Workmentioning
confidence: 99%
“…The expansion of relative advantage may include increasing the performance and benefits, as well as lowering the organization's operational expenditures (Chen & Zhang, 2016). Online food delivery services can be certainly recognized and relied on if the services are able to provide and boost efficiency and profitability as well as to reinforce the firm's competitiveness (Chen & Zhang, 2016). Hence, the intensity of the usage depends on the level of relative advantage.…”
Section: Introductionmentioning
confidence: 99%
“…The empirical results showed that environmental uncertainty played a moderating role between big data technical skills and resource integration and regulated the mediate effect of resource integration; that is, the higher the environmental uncertainty, the more big data technical skills can improve the ability of resource integration, and then improve the innovation of novel business model. Gupta and George [12] pointed out that under the uncertain environment, enterprises rely more on big data analysts to use analysis tools to capture valuable market development trend information from the big data obtained by enterprises, so as to use resources with advantages when carrying out innovation in technology, system, product and ecology [18,24] and improve the resource integration ability of enterprises. This empirical result directly responded to Skordoulis et al [23] that changes in the environment will affect the competitive advantage of enterprises, and Sirmon et al [17] that enterprises can continuously maintain their competitive advantage and value creation ability by improving their ability to allocate, combine and develop resources.…”
Section: Discussionmentioning
confidence: 99%
“…Skordoulis et al empirically showed that changes in the environment will affect the competitive advantage of enterprises through 225 valid questionnaires investigating large and medium-sized Greek companies [23]. Using quantitative data from mid-level managers and senior managers Sustainability 2022, 14, 2670 3 of 16 in 320 Chinese medical institutions, Chen and Zhang empirically demonstrated that the relationship between the relative advantage and willingness to use mHealth services was positively moderated by environmental uncertainty [24]. Considering that enterprises may rely more on the assistance of big data technical skills to integrate resources and make corresponding decisions under the scenario of environmental uncertainty, environmental uncertainty may affect the effectiveness of big data technical skills.…”
Section: Introductionmentioning
confidence: 99%